(untitled) (Research, Society and Development, 2022)
Objective: The difficulties experienced easily by nurses are not related to the care of chronic diseases and the strategies used by them for the application of a universal hospital as an application of a universal hospital. Methods: This is an exploratory-descriptive research with a qualitative approach. Thirty nurses participated in the study. It was developed in a university hospital in southern Brazil. It was carried out in December 2018. Results: The responses through the survey were separated into three distinct categories: Facilities for different hospitalized categories being traditional for adult care. personal illness, end and difficulties assists the hospitalized with chronic illness, difficulties are helped to take care of the hospital, end in the case of children and adolescents. disease are chronics listed by two categories, being practical aspects and updates. Final Considerations: Do not identify that it is necessary for the nurse to easily recognize institutional and personal factors for people and teach personal difficulties, regarding personal difficulties, identified themselves and interpersonal difficulties, regarding individual difficulties of reference and lack of experience , institutional and institutional. the overload of tasks and lack of structure and assistance difficulties and relationship between the teams.